Antioxidant Capacity and Antibacterial Activities of Leaf Extract of Adansonia digitata - Odusina , Babatope Oluseun; Chibuikem , Chidimma Mary; Osiboye , O. O. (Nigerian Journal of Pharmaceutical and Applied Science Research, 2020)
This research work investigated the antioxidant and antibacterial activities of the leaves of Adansonia digitata L.malvaceae (Baobab tree) to justify its use in traditional medicine practice. The leaf extract of Adansonia digitata (Baobab tree) was evaluated for antioxidant and antibacterial activities using 2,2- diphenyl -1-picrylhydrazyl (DPPH) method and the disc diffusion method respectively. The extract was also screened for the presence of phytochemicals. At concentration of 0.062 mg/ml, the leaves extract displayed high free radical scavenging activities. The extract was also active against all the tested bacteria but inactive against fungi at concentration of 200 to 100 mg/ml. Preliminary phytochemical tests revealed the presence of flavonoids, alkaloid and saponins. This study revealed that Adansonia digitata is a good source of antioxidants and also justifies the use of this plant in the treatment of fever, dysentery, diarrhea, inflammatory ulcers and diuretic activities due to its antibacterial activities.